Global Imperative of Suicidal Ideation in 10 Countries Amid the COVID-19 Pandemic - Cheung, Teris; Lam, Simon Ching; Lee, Paul Hong; Xiang, Yu Tao; Yip, Paul Siu Fai; , The International Research Collaboration on COVID-19 (Frontiers in Psychiatry, 2021)
Background. The novel coronavirus (COVID-19) has had a detrimental impact on individuals’ psychological well-being; however, a multi-country comparison on the prevalence of suicidal ideation due to the virus is still lacking. Objectives. To examine the prevalence and correlates of suicidal ideation among the general population across 10 countries during the COVID-19 pandemic. Materials and Methods. This was a cross-sectional study which used convenience sampling and collected data by conducting an online survey. Participants were sourced from 10 Eastern and Western countries. The Patient Health Questionnaire (PHQ-9) was used to measure the outcome variable of suicidal ideation. Ordinal regression analysis was used to identify significant predictors associated with suicidal ideation. Results: A total of 25,053 participants (22.7% male) were recruited. Results from the analysis showed that the UK and Brazil had the lowest odds of suicidal ideation compared to Macau (p< 0.05). Furthermore, younger age, male, married, and differences in health beliefs were significantly associated with suicidal ideation (p< 0.05). Conclusions: The findings highlight the need for joint international collaboration to formulate effective suicide prevention strategies in a timely manner and the need to implement online mental health promotion platforms. In doing so, the potential global rising death rates by suicide during the pandemic can be reduced.